(untitled) (Bangladesh Journal of Medical Microbiology, 2019)
The prevalence of STIs related cervicitis in Bangladesh among female sex workers (FSWs) is quite high and among them young (≤ 24 years) FSWs are more sufferers. The aim of this study was to detect infectious agents of cervicitis including Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis, Mycoplasma genitalium, Mycoplasma hominis, Ureaplasma urealyticum and Ureaplasma parvum in SWs of aged 10-24 years from endocervical swabs by multiplex real time PCR. A cross sectional study was done in collaboration with department of Microbiology, BSMMU, Dhaka and Save the Children, Bangladesh between March to December 2017 among sex workers enlisted to receive HIV prevention services at different drop in centers (DICs) in Dhaka.Total 105 SWs of aged between 10-24 years and clinically suspected as cervicitis, were enrolled for the study. Endo-cervical swabs were collected during examination and tested in dept of Microbiology, BSMMU by multiplex PCR and other tests for aforementioned pathogens. Data were collected by face to face interview using semi-structured questionnaire and clinical examinations were done using Casco’s vaginal speculum. Among the study population, 87 (82.9%) were between 20-24 years of age. On examination, out of 105, 67 (63.8%) patients had no cervical discharge, only 8 (7.6%) had muco-purulent discharge. Out of total, 95 (90.5%) patients were mPCR positive for at least one pathogen and only 3 (2.9 %) N. gonorrhoeae isolated by culture, 8(7.6%) cases of C. trachomatis were detected by DFA and 8 (7.6%) cases of T. vaginalis were detected by wet film. Among the mPCR positive (95) cases, 63(66.3%) patients had mixed infections and among them, M. hominis was the highest (76.2%) followed by U. urealyticum (49.2%). In the patients having ‘no’ (67) cervical discharge, 32 (48%) had M. homini sinfection followed by U. parvum (40%). Majority of FSWs had mixed infection and M.hominis was the highest. A high number of patients hadno cervical discharge though it is one of the diagnostic criteria for cervicitis in current syndromic management. In comparison to other available diagnostic tests, organisms were detected efficiently by multiplex PCR and could be advised routinely in such cases of mixed infection. Bangladesh J Med Microbiol 2019; 13 (1): 4-11